Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1016/j.jsat.2012.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Directly administered antiretroviral therapy: Pilot study of a structural intervention in methadone maintenance

Abstract: Devising interventions to provide integrated treatment for addiction and medical problems is an urgent issue. This study piloted a structural intervention, Directly Administered Antiretroviral Therapy (DAART), to assist methadone-maintenance patients in HIV medication adherence. Twenty-four participants received: 1) antiretroviral medications at the methadone clinic daily before receiving their methadone; 2) take-home antiretroviral medication for days they were not scheduled to attend the methadone clinic, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 23 publications
0
25
0
2
Order By: Relevance
“…Assessing virologic outcomes was limited by methodologic issues—for example, cutoffs for viral suppression varied from < 20 to < 400 copies/ml (limiting comparability), some patients met criteria for viral suppression at some time points but not longitudinally, and some studies reported viral loads but did not formally assess viral suppression. Among the 8 studies that achieved at least 80% virologic suppression [2734], the types of interventions varied [3 directly administered ART (DAART), 2 behavioral/counseling, 2 pharmacy-based and 1 education], as did the target population being addressed (6 general, 1 women, 1 PWUD), and the type of study design (4 RCTs, 1 cohort, 3 pre-post). Nonetheless, only four of these studies [27, 29, 32, 34] found a significant improvement in viral suppression in the intervention group versus the comparator group.…”
Section: Resultsmentioning
confidence: 99%
“…Assessing virologic outcomes was limited by methodologic issues—for example, cutoffs for viral suppression varied from < 20 to < 400 copies/ml (limiting comparability), some patients met criteria for viral suppression at some time points but not longitudinally, and some studies reported viral loads but did not formally assess viral suppression. Among the 8 studies that achieved at least 80% virologic suppression [2734], the types of interventions varied [3 directly administered ART (DAART), 2 behavioral/counseling, 2 pharmacy-based and 1 education], as did the target population being addressed (6 general, 1 women, 1 PWUD), and the type of study design (4 RCTs, 1 cohort, 3 pre-post). Nonetheless, only four of these studies [27, 29, 32, 34] found a significant improvement in viral suppression in the intervention group versus the comparator group.…”
Section: Resultsmentioning
confidence: 99%
“…One study is piloting a novel, multilevel Directly Administered AntiRetroviral Treatment intervention to improve long-term ART medication adherence and reduce HIV-1 RNA viral load in methadone maintenance patients (75). Another study is testing the efficacy of an on-site HIV and Hepatitis Care Coordination intervention to increase hepatitis vaccination and attendance at HIV and/or HCV medical care intake (76,77).…”
Section: Activities and Resultsmentioning
confidence: 99%
“…It was determined that directly observing therapy, as a long-term intervention strategy, requires significant up-front planning and flexibility (Sorensen et al, 2012). Alternatives such as motivational interviewing, contingency management, pill boxes, calendar marking, or cell phone reminders could be practiced in lieu of or in tandem with direct observation.…”
Section: Discussionmentioning
confidence: 99%
“…The contents and procedures of the integrated ART services were initially developed based on previous research (Achmad et al, 2009;Berg et al, 2011; Sorensen et al, 2012; Wolfe et al, 2010) and our experience with MMT providers and clients (Li et al, 2013), and were finalized collaboratively by the research team and local expert panel. The following services were designed to be delivered by the MMT clinics:

Direct observed therapy : clients on ART were encouraged to adjust their medication habits in conjunction with methadone dosage (e.g., taking ART under the direct observation of a service provider once a day).

Reminder services : all HIV-positive clients were provided reminders for routine CD4/viral load testing.

…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation